(untitled) (Development Service Industry Management, 2024)
The article examines the issues of sustainable and effective functioning and development of health care institutions. It is pointed out that in view of the functioning of health care institutions in the field of providing consumer services to the population, the formation of high-quality intellectual and human resources becomes critically important here. Therefore, despite the quality of the services themselves, the issue of managing the selection and development of personnel of health care institutions comes to the fore. Based on these principles, the purpose of the article is to develop the methodological and applied provisions of personnel management of health care institutions. A whole range of issues related to the formation of the staff, payment and stimulation of the work of the staff, movement of the staff, structural characteristics of security and development of the staff of health care institutions were considered. Conclusions have been made in terms of increasing the effectiveness of the overall improvement of personnel management processes of subjects of this type of activity. It has been proven that personnel management in the field of health care in modern conditions is the most important and key tool. It is argued that the policy of health care institutions in this area should be strategic and tactically verified, and in terms of improving the personnel potential of health care institutions, the provision of qualified employees is an important priority, increasing the stability of personnel, optimizing the use of personnel, improving working conditions and social protection, training and development of personnel, promoting innovations in the field of intellectual and personnel support. It is necessary to implement a number of basic measures that will help to improve the intellectual and personnel support of domestic medical institutions. It has been proven that one of the key tasks of personnel management in the field of health care is the improvement and development of the intellectual capabilities and abilities of employees, qualitative and quantitative changes in their structure to achieve better results in creative activities and in all areas of business processes.